On the historical development of the phonetic system of english: a linguosynergetic approach (Nexo Revista Científica, 2021)
The article advances a novel methodological approach to the study of language development, namely a diachronic synergetics. The purpose of the present research is, through disclosing synergetic features of the phonetic system, to reveal heuristic potency and applicability of principles of the synergetic paradigm to language studies. The authors claim that the phonetic system of language possesses synergetic features and it changes according to common principles of development of complex systems. The authors prove that changes in the phonetic system are neither chaotic nor random, since they are preconditioned by the features of the system itself. The theoretical significance of the present research lies in the widening of our knowledge of language as a synergetic system, and of synergetic features of the phonetic system of English, in particular. The obtained data can be fully employed practically into lectures and seminars on the history of English, theoretical phonetics, and historical linguistics.